THE INFLUENCE OF AESTHETIC IMAGE ON AESTHETIC RELATIONS AND SOCIETY ON SOCIAL NORMS - Abdurakhimov Bekhzodjon Bahromjon ugli (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation. In the article, Aesthetic image, appearance, dress culture, beauty of behavior, aesthetic qualities of a fashion item, evaluative questions about how fashion should be or "should not be" in terms of fashion and beauty today, Economy as one of the most complex systems of society’s life, the general need for endless things such as food, clothing, housing, tools and means of production and their The availability of satisfying methods has been studied.